2011
DOI: 10.1118/1.3626573
|View full text |Cite
|
Sign up to set email alerts
|

Design, manufacture, and evaluation of an anthropomorphic pelvic phantom purpose-built for radiotherapy dosimetric intercomparison

Abstract: The phantom constructed for the present study incorporates all characteristics necessary for accurate Level III intercomparison studies. Following use in an extensive Level III dosimetric comparison over a large time scale and geographic area, the phantom retained mechanical stability and did not show signs of radiation-induced degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…• There were some design and manufacturing anomalies in the phantom that have been described elsewhere. 12 The ability to replace dosimetric materials between irradiations without repositioning the phantom saved considerable time during the measurement process. • The undertaking of this study has allowed estimates to be made of the uncertainties inherent in utilising reported dosimetry as a surrogate for actual patient dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…• There were some design and manufacturing anomalies in the phantom that have been described elsewhere. 12 The ability to replace dosimetric materials between irradiations without repositioning the phantom saved considerable time during the measurement process. • The undertaking of this study has allowed estimates to be made of the uncertainties inherent in utilising reported dosimetry as a surrogate for actual patient dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…Consistency in EBRT dose delivery was assessed via dosimetric audit of centres [3][4][5][6][7] and adherence to trial planning protocol via expert review of each treatment plan [8].…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…The RPC is not the only QA service to use anthropomorphic body-parts. Harrison et al [21] described the use of a pelvic phantom for an Australian multicenter radiotherapy dosimetry comparison [22]. The Australian pelvic phantom was a solid phantom that had structures representing bone, organ and backfill and it could accommodate the placement of TLD and an ion chamber at various locations.…”
Section: Commercially Available Anthropomorphic Body-part Phantomsmentioning
confidence: 99%